PERANCANGAN APLIKASI SISTEM INFORMASI REKAM MEDIS PADA PUSKESMAS MAJASARI PANDEGLANG BERBASIS WEB - Aulia Rahmat Ramadhani (2020)
Every Puskesmas must have an obligation to have an Information System, following the Regulation of the Ministry of Health of the Republic of Indonesia number 43 of 2019 article 62 paragraph 1, some targets must be achieved by the Puskesmas to obtain accreditation, one of which is that they must have a Medical Record Information System. The purpose of this study is expected that with the Application of Medical Record Information System at Majasari Health Center, Pandeglang based on the website, the Medical Record service at Majasari Health Center can run more efficiently and effectively. The method used in this research is to use the RAD method (Rapid Application Development) stages carried out in this research are the study of literature, identification of problems, data collection, system analysis, RAD method, and finally the documentation, the purpose of using the RAD method is to shorten the time required in the system development life cycle between the design and application of information systems to be made. The results of the study are in the form of a web-based Medical Record Information System application that is useful to help health workers in the Majasari Public Health Center, Pandeglang.